Development of Teacher Competence in Improving 21st Century Learning in Santa Lusia Kindergarten - Saloma Banjarnahor; Yuniarto Mujisusatyo; Wanapri Pangaribuan; Isli Iriani Indiah Pane (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The teacher's limited knowledge of 21st century learning skills is an obstacle to implementation in the classroom. In the educational context, technological developments should have had a positive impact on the learning process as well as from the perspective of teacher competency development. Less than ideal conditions occur in school, where the competence of the teachers is still weak. Teaching is still conventional and teacher-centered. The solution to overcome this problem is to attend training organized by the foundation. The research method used is descriptive quantitative. The subjects in this study were Santa Lucia Kindergarten Teachers. Data analysis used in this research is data reduction, data presentation, and conclusion. The results of this study cannot be disclosed because the research has not been completed. This research is in the nature of product development for the benefit of the competence of all teachers in the Santa Lucia Kindergarten Unit. The results of the education and training that have been carried out have not been carried out in full, its implementation is still in progress. The author concludes that teachers in today's 21st century educational development have more severe challenges and their tasks are more complex. The role of the teacher is very important in managing the learning process, to face these challenges, therefore teachers must have the ability to think critically, social responsibility, the ability to build networks, time discipline and rules as well as skills, skills in the 21st century.